Effcts of federal reserve interest rates on stock markets. - Chew, Jackie Pei Pei. (2013)
This project attempts to study the effects of Federal interest rates in the movements in the stock markets, namely the New York stock market, which has a certain effect on regional stock markets in Asia Pacific region. We will be examining Singapore and Hong Kong market mainly to find out the relationship between these markets and will attempt to derive at a conclusion.